Macrophage susceptibility to infection by Ghanaian Mycobacterium tuberculosis complex lineages 4 and 5 varies with self-reported ethnicity - Osei-Wusu, Stephen; Tetteh, John K. A.; Musah, Abdul Basit; Ntiamoah, Desmond Opoku; Arthur, Nelly; Adjei, Abraham; Arbues, Ainhoa; Ofori, Ebenezer Addo; Mensah, Kwadwo Akyea; Galevo, Sutaya Elsie Afua; Frempong, Abena Frema; Asare, Prince; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background The epidemiology of Mycobacterium tuberculosis complex (MTBC) lineage 5 (L5) infections in Ghana revealed a significantly increased prevalence in Ewes compared to other self-reported ethnic groups. In that context, we sought to investigate the early phase of tuberculosis (TB) infection using ex vivo infection of macrophages derived from the blood of Ewe and Akan ethnic group volunteers with MTBC L4 and L5 strains. Methods The study participants consisted of 16 controls, among which self-reported Akan and Ewe ethnicity was equally represented, as well as 20 cured TB cases consisting of 11 Akans and 9 Ewes. Peripheral blood mononuclear cells were isolated from both healthy controls and cured TB cases. CD14+ monocytes were isolated and differentiated into monocyte-derived macrophages (MDMs) before infection with L4 or L5 endemic strains. The bacterial load was assessed after 2 hours (uptake) as well as 3 and 7 days post-infection. Results We observed a higher capacity of MDMs from Ewes to phagocytose L4 strains (p < 0.001), translating into a higher bacillary load on day 7 (p < 0.001) compared to L5, despite the higher replication rate of L5 in Ewe MDMs (fold change: 1.4 vs. 1.2, p = 0.03) among the controls. On the contrary, within macrophages from Akans, we observed a significantly higher phagocytic uptake of L5 (p < 0.001) compared to L4, also translating into a higher load on day 7 (p = 0.04). However, the replication rate of L4 in Akan MDMs was higher than that of L5 (fold change: L4 = 1.2, L4 = 1.1, p = 0.04). Although there was no significant difference in the uptake of L4 and L5 among cured TB cases, there was a higher bacterial load of both L4 (p = 0.02) and L5 (p = 0.02) on day 7 in Ewe MDMs. Conclusion Our results suggest that host ethnicity (driven by host genetic diversity), MTBC genetic diversity, and individual TB infection history are all acting together to modulate the outcome of macrophage infections by MTBC.